SOCIAL PRESENCE IS NO LONGER A FACTOR IN CUSTOMER TRUST IN SHOPPING FOR LIVE STREAMING E-COMMERCE - Calysta, Netha Eliana; Suade, Yuyun Karystin Meilisa (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
The surge in online shopping via e-commerce live streaming, particularly evident since the COVID-19 pandemic, has transformed consumer behavior. Data shows that a staggering 83.7% of Indonesians were engaged in this activity in 2022. This study aims to examine the factors influencing purchase intent among Makassar students within this context. It also explores the interrelationships between these variables and purchase intention. Specifically, the research investigates the impact of interaction, entertainment, social presence, and trust on consumer trust and subsequent purchase behavior. Employing a quantitative methodology with a sample size of 215 students, the study found that interaction and entertainment positively correlated with consumer trust. Conversely, social presence exerted no significant influence. Importantly, trust emerged as a key determinant of purchase intention.